THE IMPORTANCE AND STATE OF ECONOMETRIC MODELING IN FORECASTING THE DEVELOPMENT DYNAMICS OF THE CHEMICAL INDUSTRY (World Economics and Finance Bulletin, 2025)
The article models the dynamics of the chemical industry development using econometric models. Initially, the article provides a brief description of scientific sources related to the topic. Then, issues such as the regression model, determination, correlation coefficients, the Durbin-Watson test, and empirical probability regarding the Fisher criterion are discussed. In the final section of the article, all the obtained results are summarized
Keywords: chemical industry; mining industry; development dynamics